Hubungan Sosial Ekonomi dan Budaya terhadap Partisipasi Ibu Rumah Tangga dalam Pengelolaan Sampah di Kecamatan Bangkinang - Hayana . (Jurnal Kesehatan Komunitas, 2015)
Components of the waste generated in the city Bangkinang for three consecutive years in 2008 was 147.25 m3 in 2009 was 167.36 m3, the year 2010 was 188.95 m3. The volume of waste from three years increase quite high because lack of community participation in managing the garbage and lack of public awareness to refineries waste into productive items such as the utilization of organic waste (composting), the use of plastic waste into 3R (Reduce , Reuse, Recycle). The purpose of this study was to analyze the relationship between socio-economic (education, income, occupation) and cultural (knowledge, habits) to the participation of housewives in waste management in the District Bangkinang Kampar regency. This study is an analytic with cross sectional design. Population is the mother-housewife who lives in District Bangkinang many as 4782 people. Samples of is 100 mother-housewife and sampling in this research is random sampling system. Collecting data with interviews and observations were based on the questionnaire. Data analysis is done by using univariate, bivariate using chi square test and multivariate. The results showed that there was a relationship between education, revenue, work, knowledge and habits for housewives participation in waste management.